The impact of kahoot-based formative assessment on student learning outcomes at a Junior High School in Samarinda - Lia Rahmayana; Abdul Halim (Universitas Merdeka Malang, 2024)
This study explores the impact of using Kahoot! as a formative assessment tool on student learning outcomes in English at SMPN 22 Samarinda. The research utilized a quasi-experimental design with pre- and post-test measures on Class VII-7 B. Findings revealed that Kahoot! significantly improved students' understanding of English grammar, particularly tenses. Data analysis was conducted using SPSS software, showing a notable increase in student achievement post-intervention. The study emphasizes the importance of integrating technology like Kahoot! in the classroom to enhance learning. Recommendations for future research and teacher strategies are also provided.